2020
DOI: 10.1590/fst.32918
|View full text |Cite
|
Sign up to set email alerts
|

Staple food crops from Brazilian Biofortification Program have high protein quality and hypoglycemic action in Wistar rats

Abstract: Biofortified staple food crops have become an effective tool by which to address micronutrient deficiencies in many at-risk populations. The effect of these food crops on the micronutrient status has been evaluated, however there is no studies investigating their protein quality, neither by themselves or in a food combination. Thus, this study investigated the effect of combinations of beans and rice, target for biofortification, with high carotenoids content crops (sweet potato and pumpkin) on protein quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the HMT modification technology, there were few reports about the HMT on sweet potato powder, but there were more reports about the entire flour rich in cellulose, ascorbic acid, sweet potato polysaccharide, minerals, phenolic substances and aldehydes and experiments in functional foods (Santos et al, 2019;Kourouma et al, 2020;Cartier et al, 2017;Franco et al, 2020;Dias et al, 2020). Therefore, HMT may not only improve the stability of the sweet potato flour products and maintain the low digestion characteristics of starch, but also the nutritional and functional characteristics of the sweet potato flour will have an important impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…In the HMT modification technology, there were few reports about the HMT on sweet potato powder, but there were more reports about the entire flour rich in cellulose, ascorbic acid, sweet potato polysaccharide, minerals, phenolic substances and aldehydes and experiments in functional foods (Santos et al, 2019;Kourouma et al, 2020;Cartier et al, 2017;Franco et al, 2020;Dias et al, 2020). Therefore, HMT may not only improve the stability of the sweet potato flour products and maintain the low digestion characteristics of starch, but also the nutritional and functional characteristics of the sweet potato flour will have an important impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Peaches as a source of food-derived proteins are mainly produced in China. However, most of peaches are discarded as wastes in peach processing industry (Koprivica et al, 2018;Ishimoto et al, 2020;Dias et al, 2020;Florêncio et al, 2020). Particularly, the annually yield of peach is about 5 million kilograms in Tibet of China.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main treatment plan for osteosarcoma is primary tumor resection combined with preoperative and postoperative chemotherapy, which increases the 5-year survival rate of osteosarcoma patients to 60% to 70% (Marec-Berard et al, 2020;Schott et al, 2018;Vaseenon et al, 2017). It is reported that high protein diet has a certain effect on postoperative nursing of patients with osteosarcoma (Dias et al, 2020;Cordeiro et al, 2020;Gavião et al, 2021;Zhou et al, 2021). In recent years, the treatment strategy for osteosarcoma has been greatly improved, but the overall survival of osteosarcoma patients is still not optimistic, which is closely related to the relatively low clinical early diagnosis rate (Lin et al, 2019;Sugiura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%